Development of An Instrument to Assess Decision Making Among Persons With and Without Traumatic Brain Injuries - Manley Beamon, Holly (East Carolina University, 2020)
This dissertation discusses existing tools for the assessment of decision making in adolescents and young adults who have sustained a traumatic brain injury (TBI) and limitations of these tools. To address these limitations, I developed an instrument named the Capacity for Decision Making Assessment, Adolescent Version (CDMA-A) which is presented, along with the initial reliability and validity data for use of this instrument as a measure of decision making. I examined descriptive statistics and internal consistency, and an exploratory factor analysis (EFA) was attempted to examine the structure of the scale. ROC Curves were developed for each item to examine predictive accuracy. In addition, differences between those with and without TBI were examined using independent samples t-tests. Other variables examined were sex differences and differences based on severity of TBI and time since initial TBI diagnosis. Findings suggested that participants with no previous history of TBI performed better on the CDMA-A decision making instrument than did participants who have experienced a TBI/concussion in the past. Significant differences were not found among severity of TBI or time since TBI. Issues with the data suggest that additional research is needed to explore scores on the CDMA-A in a larger sample and that revisions to the items may be required before the CDMA-A could be considered a reliable and valid measure of judgment and decision making for adolescents and young adults.
Keywords: Traumatic Brain Injuries; Decision making in adolescence--Testing; Brain damage--Patients; Adolescent psychology